2016
DOI: 10.1038/srep26277
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthetic bupivacaine induced ovarian and prostate cancer apoptotic cell death and underlying mechanisms in vitro

Abstract: Retrospective studies indicate that the use of regional anesthesia can reduce cancer recurrence after surgery which could be due to ranging from immune function preservation to direct molecular mechanisms. This study was to investigate the effects of bupivacaine on ovarian and prostate cancer cell biology and the underlying molecular mechanisms. Cell viability, proliferation and migration of ovarian carcinoma (SKOV-3) and prostate carcinoma (PC-3) were examined following treatment with bupivacaine. Cleaved cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 47 publications
(52 reference statements)
6
62
1
Order By: Relevance
“…However, the reduction in cell viability measured by CellTiter-Blue ® for ropivacaine at 1,000 µM corresponds to a reduction in cell proliferation measured by PKH67 at the same concentration. Xuan et al reported similar findings in ovarian and prostate cancer cell lines (19). In their study, only bupivacaine at 1 mM decreased cell viability significantly, but not at lower concentrations.…”
Section: Discussionsupporting
confidence: 64%
“…However, the reduction in cell viability measured by CellTiter-Blue ® for ropivacaine at 1,000 µM corresponds to a reduction in cell proliferation measured by PKH67 at the same concentration. Xuan et al reported similar findings in ovarian and prostate cancer cell lines (19). In their study, only bupivacaine at 1 mM decreased cell viability significantly, but not at lower concentrations.…”
Section: Discussionsupporting
confidence: 64%
“…In in vitro studies examining local anaesthetic effects on metastatic colon cancer cells, ropivacaine demonstrated inhibitory properties to these cells . Thus, the higher cancer specific mortality suggested in this follow‐up analysis was surprising …”
Section: Discussionmentioning
confidence: 71%
“…This has led to the changes in the way that perioperative providers care for patients undergoing cancer surgery including tailoring anaesthetic and surgical techniques to minimize the activation of systemic inflammatory pathways and hence reduce the stress response to the procedure . Studies examining the effects of local anaesthetics on ovarian, prostate and gastric cancer have all shown ‘anti‐cancer’ properties of the local anaesthetic . In in vitro studies examining local anaesthetic effects on metastatic colon cancer cells, ropivacaine demonstrated inhibitory properties to these cells .…”
Section: Discussionmentioning
confidence: 99%
“…Although the immunosuppressive effect of opioids has been widely documented, some reports argue that opioids' immunomodulatory effects may be beneficial in the context of malignancy [16][17][18]. The effects of opioids on neoplasia progression likely depend on the extent of their analgesic action, counterbalancing their immunomodulatory effect by decreasing acute pain and attenuating the stress response.…”
Section: Mechanism Favoring Type Of Anesthesia and Cancer Recurrencementioning
confidence: 99%
“…Regional anesthesia also decreases the need for perioperative opioids, which are believed to have a protumoral effect [14,15]. In addition, studies on bupivacaine suggest that it has direct anti-neoplastic properties via activation of both intrinsic and extrinsic apoptotic pathways in ovarian cancer and the intrinsic pathway in prostate cancer [16]. Still, confounding evidence must be taken into account.…”
Section: The Effect Of Regional Anesthesia On Cancer Recurrencementioning
confidence: 99%